Classification for coefficient of variation in physical attributes of arabic coffee seedling - Campos, Bernardo de Paula; Nascimento, Thais Santana do; Nascimento, Adriel Lima; Bonelá, Édlen dos Santos; Grobério, Rafaela Barreto Cazaroto; Schmildt, Edilson Romais (Brazilian Journal of Production Engineering, 2024)
The coefficient of variation (CV) is an important measure of the variability of experimental results and can be useful in defining the number of assay repetitions necessary to detect a difference between treatment means common to a given probability. The Pimentel-Gomes (2009) classification categorizes CV values ​​as low, medium, high and very high, where lower values ​​indicate greater precision. However, this classification, originally developed for experiments with sugarcane cultivation, is currently being applied indiscriminately to coefficients of variation of different variables in different crops, making it essential to update the classification of CV values, adapted to the diversity of species. Since no study specifically addressed the physical attributes of Arabica coffee seedlings, this study seeks to establish CV classification ranges for eight physical attributes of coffee seedlings of this variety, using data from 72 scientific publications (2003-2023) via bibliometric research. The experimental precision for the physical attributes of coffee seedlings can be measured based on the coefficient of variation, being an important tool in studies for the crop, attesting to the reliability of the experiment.